The Topography of Robbery: Does Slope Matter? - Haberman, Cory P. (Journal of quantitative criminology, 2021)
Objectives To examine the influence of street block slope on robbery in Cincinnati, Ohio. Methods Data visualizations were used to examine how street block slope varies across the city. Negative binomial regression models were used to estimate the influence of street block slope on robbery net of betweenness, facility composition, and socio-demographics. Results A 1% increase in street block slope was associated with roughly 4.5% fewer street block robberies per foot of street block length. Street blocks with a higher expected usage potential, measured via betweenness, were also observed to have higher expected robbery levels. In addition, numerous facilities and neighborhood socio-demographic characteristics linked to higher robbery levels. Conclusions Steeper street blocks may have fewer robberies because they make the physical costs for committing robberies too high, are too difficult to escape from, and/or provide fewer robbery opportunities due to relatively lower usage. Moreover, more robberies appear to occur on street blocks with higher betweenness due to more potential opportunities there. Finally, the influence of facilities and community characteristics were largely consistent with theoretical expectations and past studies. Future studies should continue to examine how topography influences aggregate crime levels and offender decision making in other settings to bolster the external validity of the present findings.